Implementasi Adaptasi Teknologi Dalam Pembelajaran di Kelas X dan XII Geologi Pertambangan SMKN 4 Palangka Raya - Metahartama, Aplus; Marcheleno, Erick; Brianto, Hendrik; Holdy, Johanes Kristian; Tundan, Jonathan A.; Sopian, Mohammad; Silitonga, Nova L.; Kahanjak, Yulius (Universitas Negeri Gorontalo, 2026)
Technology adaptation activities in learning were carried out in Grade XII of SMKN 4 Palangka Raya through the Teaching Campus Program. This activity aimed to introduce and improve students’ understanding of various technologies and software that support the learning process and are relevant to industry needs. The technology adaptation activities included the introduction of ArcGIS, Surpac, and Surfer software, basic drone operation training, and the use of the Canva application as a supporting learning medium. The activities were implemented in stages through material introduction, hands-on practice, and evaluation. Students were actively involved in each activity to understand the basic functions of each technology and their application in learning. The results indicate that students gained basic knowledge and skills in using learning technologies and began to understand the relevance between school learning materials and their application in the workplace. These technology adaptation activities are expected to enhance students’ readiness for internships and future careers, particularly in the field of geology and mining.